ADVANCED INTERNATIONAL EXPERIENCES IN MANAGING BUSINESS ENTITIES (INTERNATIONAL JOURNAL OF SCIENCE AND TECHNOLOGY, 2025)
This article examines the management styles of entrepreneurial entities on an international scale, focusing on developed countries. The analysis explores various factors within the management system, including culture, economic conditions, and the differences between small and large business management. Additionally, a model has been developed based on research findings, and studies conducted within the scope of the topic have been analyzed, leading to relevant conclusions.